The Repercussions of Brexit for CARICOM's Cohesion. Issue 5 (2nd September 2016) - Lewis, Patsy
Abstract: Britain's decision to leave the European Union has sent shockwaves not just within Europe but across the globe. In the Caribbean, it has heightened uncertainty about the Caribbean Community's (CARICOM) ability to survive its own fissures, most recently expressed in Jamaica's decision to review its membership of CARICOM. This article explores some of the challenges CARICOM is experiencing, in particular Jamaica's dissatisfaction with and position within the group. It argues that despite parallels between Britain and Jamaica and their position in their respective groupings, the rationale for CARICOM is fundamentally different from that underlying the European integration experience. It concludes that CARICOM is unlikely to unfurl because the factors driving the process—small size, global marginality and common challenges—provide a strong impetus for their cohesion.